2010
DOI: 10.1016/j.mam.2009.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic pathways in tumor mitochondria as targets for cancer therapy and the importance of the ROS-induced apoptotic trigger

Abstract: Mitochondria are emerging as idealized targets for anti-cancer drugs. One reason for this is that although these organelles are inherent to all cells, drugs are being developed that selectively target the mitochondria of malignant cells without adversely affecting those of normal cells. Such anti-cancer drugs destabilize cancer cell mitochondria and these compounds are referred to as mitocans, classified into several groups according to their mode of action and the location or nature of their specific drug tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(98 citation statements)
references
References 258 publications
(286 reference statements)
2
95
0
1
Order By: Relevance
“…Recently, it is reported that Akt in human cancer induced the glycolytic phenotype in cancer cells by phosphorylating hexokinase II to increase its association with voltage-dependent anion channel on the mitochondrial outer membrane (50). The actions of Akt render the cancer cell dependent on the availability of glucose for survival (50). Our study suggests palmitic acid is transferred from adipocytes and activates Akt in melanoma cells.…”
Section: Table 2 Cell Cycle Distributions In Melanoma Cellsmentioning
confidence: 59%
See 1 more Smart Citation
“…Recently, it is reported that Akt in human cancer induced the glycolytic phenotype in cancer cells by phosphorylating hexokinase II to increase its association with voltage-dependent anion channel on the mitochondrial outer membrane (50). The actions of Akt render the cancer cell dependent on the availability of glucose for survival (50). Our study suggests palmitic acid is transferred from adipocytes and activates Akt in melanoma cells.…”
Section: Table 2 Cell Cycle Distributions In Melanoma Cellsmentioning
confidence: 59%
“…Akt signaling has been reported to regulate melanoma cell survival, migration, and metastasis and contribute to melanoma chemoresistance to therapy (29,49). Recently, it is reported that Akt in human cancer induced the glycolytic phenotype in cancer cells by phosphorylating hexokinase II to increase its association with voltage-dependent anion channel on the mitochondrial outer membrane (50). The actions of Akt render the cancer cell dependent on the availability of glucose for survival (50).…”
Section: Table 2 Cell Cycle Distributions In Melanoma Cellsmentioning
confidence: 99%
“…OGDH is a well-characterized auto-antigen in primary biliary cirrhosis. The activity of the enzyme is much lower in Alzheimer's disease, and there are reports of the enzyme's susceptibility to modification by oxidative stress [29] . Inhibition of OGDH activity alleviates glutamate-induced calcium deregulation, mitochondrial depolarization, and neuronal death [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Many pharmacological agents able to specifically target these organelles in malignant cells without affecting their normal counterparts are being developed (Ralph et al, 2010). The tumor suppression of mitochondrial respiration would decrease endogenous ROS generation, as inhibition of H þ -ATP synthase has been shown to delay ROSdependent cell death (Santamaria et al, 2006).…”
Section: The Rise Of Anticancer Therapeutics Targeting Metabolismmentioning
confidence: 99%